Evaluation of Chemical Health and Safety Practices and Exposure Risks in Undergraduate Chemistry Laboratory Practicum - Mutiah Ulfah; Vladimir Morozov; Dinesha Dabera (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: This study aims to evaluate the implementation of chemical health and safety practices in undergraduate chemistry laboratory practicum by focusing on chemical hazard identification and exposure risk assessment associated with laboratory activities involving hazardous substances. Methodology: The research employed a descriptive observational design using a structured chemical safety checklist and a task-based risk assessment approach. The evaluation considered chemical properties such as toxicity, flammability, and corrosivity, as well as potential exposure pathways including inhalation, dermal contact, and accidental ingestion. Laboratory activities were analyzed based on the likelihood of exposure and the severity of potential health impacts to determine risk levels. Main Findings: The results indicate that, although overall safety practices were categorized as acceptable, several laboratory activities involving hazardous chemicals such as nitric acid, sulfuric acid, and benzene present significant chemical exposure risks. High-risk conditions were mainly associated with improper handling of corrosive and flammable substances and inconsistent use of personal protective equipment. These conditions suggest the presence of both acute exposure risks, including chemical burns and irritation, and potential chronic health risks due to repeated low-level exposure in laboratory environments. Novelty/Originality of this study: This study contributes to chemical health risk prevention by integrating chemical hazard characteristics and exposure pathways into a task-based risk assessment framework in an academic laboratory setting. Unlike previous studies that primarily focus on general safety practices, this research emphasizes exposure-based chemical health risk evaluation, providing a more comprehensive approach to improving chemical safety management in chemistry laboratory education.